Technical challenges of plug-in hybrid electric vehicles deployment in smart electric grid - Rahman, I. (Hikari Ltd., 2015)
Recent transportation system faces major renovation on the way to electrification with the combination of recently developed smart electric grid for attaining carbon-free and sustainable future. In this wake, Plug-in Hybrid Electric Vehicles (PHEVs) are gaining establishment as an environment friendly alternative to traditional vehicle and playing a crucial role in improving the overall fuel efficiency. Discontinuous renewable energy resources can be combined efficiently to the electric grid by the higher participation of PHEVs in the roads. Formation of appropriate charging infrastructures alongside optimum charging regulation is essential for further achievement in highway transportation system. This paper reports technological challenges of PHEVs adoption in the smart electric grid system and proposes future guidelines for researchers in the domain of plug-in hybrid electric vehicle. Â© 2015 Imran Rahman, Pandian Vasant and Balbir Singh Mahinder Singh and M. Abdullah-Al-Wadud.